Medical cannabis in autism spectrum disorder: a specialist perspective. (2nd October 2022) - Erridge, Simon; Sodergren, Mikael H; Rucker, James J
Abstract : Autism spectrum disorder (ASD) is a pervasive developmental disorder that is thought to affect 52 million people globally. Individuals are commonly affected by comorbid behavioural difficulties and psychiatric conditions. However, when considering the tolerability of currently available licensed medications, there are limited treatments for ASD. Cannabis-based medicinal products (CBMPs) have been proposed as a potential novel therapeutic for ASD based on the pre-clinical evidence of the effects of cannabinoids on anxiety, mood, behaviour and motor skills. However, clinical translation has been limited. Moreover, studies suggest that CBMPs are well tolerated by those with ASD. While randomised controlled trials are still necessary, those with ASD can be considered for treatment with CBMPs if they have failed to respond to licensed therapies following assessment at a specialist clinic, such as Sapphire Medical Clinics.